PENGARUH PENALARAN MORAL DAN INTENSITAS MORAL TERHADAP SKEPTISME PROFESIONAL AUDITOR PEMERINTAH - , Supeni Anggraeni Mapuasari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Auditor professional skepticism is a core concept in audit codes of ethics. This research tries to elaborate the influence of ethics to auditor professional skepticism. Components of ethics being tested in this research are moral reasoning and perceived importance of moral intent. Moral reasoning is an individual moral development level that reflects how human perceive right and wrong when facing ethical dilema. Moral intent reflects Intensitas the importance of understanding the characteristics of moral issues when facing audit dilema. Theory of cognitive dissonance was utilized to explain this research analysis. The respondents of this research are auditors of Indonesian Supreme Audit Institution (SAI). Questionnaries were spread of in the SAI training institution. The auditors were came from varies provinces in Indonesia. The result of this study found a positive relationship between moral reasoning and auditor professional skepticism. On the other side, it failed to proof the relationship between moral intent and auditor professional skepticism. This research confirms the implication of cognitive dissonance theory to explain the relationship between moral reasoning and skepticim. It implies the importance of moral reasoning to be concerned by BPK as the audit external institution in Indonesianâs government.